2010
DOI: 10.1111/j.1600-051x.2010.01628.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the neutrophil respiratory burst by plasma from periodontitis patients is mediated by pro-inflammatory cytokines

Abstract: This study demonstrates that plasma cytokines may have a role in inducing the hyperactive (IL-8, GM-CSF, IFN-α) and hyper-reactive (IFN-α) neutrophil phenotype seen in periodontitis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 36 publications
2
71
0
1
Order By: Relevance
“…IL-8 in immune-related cells, such as endothelial cells, macrophages, mast cells, and keratinocytes (K€ ohidai and Csaba, 1998), can also induce a series of physiological reactions required for phagocytosis and migration, such as increasing the intracellular concentration of Ca 21 (Mahali et al, 2011), exocytosis (Yasuda et al, 2012), and respiratory bursts (Dias et al, 2011). Previous studies indicated that nickel can trigger activation of intracellular reactive oxygen species (ROS) (Oller, 2002;Stejskal et al, 2006;Freitas et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…IL-8 in immune-related cells, such as endothelial cells, macrophages, mast cells, and keratinocytes (K€ ohidai and Csaba, 1998), can also induce a series of physiological reactions required for phagocytosis and migration, such as increasing the intracellular concentration of Ca 21 (Mahali et al, 2011), exocytosis (Yasuda et al, 2012), and respiratory bursts (Dias et al, 2011). Previous studies indicated that nickel can trigger activation of intracellular reactive oxygen species (ROS) (Oller, 2002;Stejskal et al, 2006;Freitas et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Phagocytosis and respiratory burst activity of leukocytes can also be substantially augmented by various proinflammatory cytokines such as IL-8, IL-1β, TNF-α, IL-6 etc. (Reato et al 2004;Dias et al 2011;Hellberg et al 2011). No data are available on the effects of sulbactam on cytokine activity; however, studies indicated that amoxicillin treatment up-regulates the expression of IL-8, TNF-α, IL-1β, IL-6 and IL-10 in response to many bacterial infections (Reato et al 1999;Melhus and Ryan, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils in AgP are in a hyperactive, primed state. 16 This hyperactivity may be attributed to circulating factors 15 or genetic make-up of individual or environmental effects. 32 These hyper responsive neutrophils may explain the difference in ROS production between patients with AgP or CP, observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils from patients with AgP are hyperactive and primed and appear to release enhanced levels of oxygen radicals, inflammatory mediators such as cytokines and matrix-degrading enzymes. 14,15 This hyperactivity and reactivity of neutrophils destroys the adjacent host tissues and contributes to the destructive changes observed in inflammatory periodontitis. 16 An excess of ROS can cause oxidative stress and damage to critical biomolecules resulting in deleterious biological effects.…”
Section: Introductionmentioning
confidence: 99%